Assessment of spinopelvic relationship among Turkish orthopedic surgeons in total joint replacement: a survey - Bostancı, Bilal; Azboy, Nesrullah; Yılmaz, Mehmet Kürşat; Çaçan, Mehmet Akif; Azboy, İbrahim (My University, 2024)
Objective: This study aims to investigate the preferences of orthopedics and traumatology specialists in evaluating the spinopelvic relationship in primary total hip arthroplasty (THA) in Türkiye. Methods: Members of the Turkish Orthopedics and Traumatology Association (n = 2485) were invited to fill out the questionnaire. The survey was created using Google Forms and distributed to participants via WhatsApp and Gmail by sharing the link. A total of 205 orthopedic surgeons responded and completed the questionnaire. The survey included 13 questions about the duration of their experience, the number of THA and spinal instrumentation procedures they performed, the dislocation rates they encountered after surgery, and the radiological assessments they performed for the spinopelvic relationship. Results: Sixty-three percent of the participants evaluated spinopelvic parameters in patients undergoing THA. Forty-seven percent of surgeons state that in their daily practice, they determine the angle of the acetabular component according to whether the spinal deformity is rigid, flexible, balanced, or unstable. While 88% of the participants stated the rate of encountering dislocation after primary THA as less than 2%, 12% of the participants stated it as more than 2%. It was observed that 40% of the surgeons with a prosthetic dislocation rate of more than 2% evaluated the spinopelvic relationship, while 67% of the surgeons with a dislocation rate of less than 2% evaluated the spinopelvic relationship. Conclusion: Approximately half of the orthopedic surgeons in Türkiye plan component placement in primary THA cases by considering the spinopelvic relationship. In order to increase awareness about the spinopelvic relationship, it would be beneficial to give more space to this subject in training programs and conferences. Level of Evidence: N/A.
Keywords: Arthroplasty; Dislocation; Hip; Questionnaire; Spinopelvic